Experimental hydrodynamics of fast-floating aquatic animals - Babenko, V. V. (Viktor Vitalevich) (Academic Press, 2020)
Experimental Hydrodynamics of Fast-Floating Aquatic Animals presents the latest research on the physiological, morphological and evolutionary factors in aquatic animal locomotion. Beginning with an overview on how to conduct experiments on swimming aquatic animals, assessing hydrodynamic forces, resistance and geometric parameters of animal bodies, the book then details how aquatic animals, such as fast-moving dolphins, can achieve high speeds without over-expelling their energy resources. It provides insights into investigations on how animals, including dolphins, sharks and swordfish can maneuver through water at high speeds, offering a natural model for improving human and technological underwater locomotion. This book is essential for researchers and practicing biologists interested in the study of aquatic animal locomotive physiology and its application to human technology. Advanced undergraduate and graduate students will also find this a helpful academic resource for further understanding animal hydrodynamics.